A tale of two ponds, Newfoundland, Canada - Leitch, Alison M.; Chen, Jianguang; Rashid, Harunur (Atlantic Geoscience, 2025)
Bathymetric surveys of two small lakes in Newfoundland, located in different environments and separated by hundreds of kilometres, were carried out using two different survey methods—ground penetrating radar (GPR) and sound navigation and ranging (sonar). The different structures of these two disparate ponds were found to be related to the differing geology and degrees of anthropogenic influence at the two locations. In addition, the study outlined the strengths and limitations of the two survey methods. Tipping’s Pond, on the outskirts of the town of Corner Brook in western Newfoundland, is a sinkhole in a popular recreation area. It is roughly square with an area of 1.6 km2 and is slightly salty, making it largely impenetrable by radar. Bathymetric surveys with a salinity-impervious fish-finder sonar system revealed Tipping’s Pond to be bowl-shaped and more than 25 m deep in the centre. Grassy Pond, 3 km inland from the Trans-Canada Highway in eastern Newfoundland, is within an undeveloped area accessible by snowmobile in the winter. It has an irregular, elongated shape 1.2 km2 in area and is very fresh. As well as determining the bathymetry, GPR was able to determine the depth of a soft sediment layer overlying till, and to image structures within the soft sediments. The top of the sediment layer is undulating and shallow (<2.9 m deep) whereas the base of the sediments overlies sub-basins about 8 m deep.